The Fiqh Paradigm in Strengthening Moderate Religiosity Through The Study of Kitab Turats in Pesantren - Yazid, M. Aba; Saiful Hidayat, Muhamad; Islamy, Athoillah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
The purpose research is to find out the transmission of the fiqh paradigm in strengthening moderate religiosity through the study of kitab turats at Hidayatul Mubtadi'en Pekalongan Islamic Boarding School. Data were obtained through observation, interviews and documentation. This study confirms that the study of the book of Turats contains the dimensions of fiqh as a paradigm for strengthening the religiosity of its students, including the value of hifz'ird in strengthening humanist religiosity through the transformation of anti-violence values (al la unf) from the material of the book of Birrul Walidain and Tarbiyatul Walad. This value transformation can equip an ethical paradigm in upholding human values. The value of hifz ummah in strengthening pluralist diversity through the transformation of the value of tasamuh (tolerance), and i'tiraf al-'urf (friendly to culture) from the material in kitab at-Tibyan and kitab Hujjah Ahlussunnah wal Jama'ah. This value transformation can equip students to have an ethical paradigm in behavior and beliefs that respect social and cultural diversity. Furthermore, the value of hifz waton in strengthening nationalist religiosity through the transformation of the value of love for the homeland (al-muwathanah) from the material of Kitab at-Tahliyah wa at-Targhib and Kitab Mukhtarul Ahadith. This value transformation can equip students to have an ethical paradigm in the form of moderate attitudes and views in maintaining the integration of state life. The findings of this study confirm that the values of maqasid sharia and tarbiyah can be integrated in the transmission of moderate religious education in Islamic education activities.